Advances in chemical physics (Wiley, 2002)
This series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. Volume 129 in the series continues to report recent advances with significant, up-to-date chapters by internationally recognized researchers.